Long-term safety and efficacy of fecal microbiota transplantation in 74 children: A single-center retrospective study - Zou, Biao; Liu, Sheng-Xuan; Li, Xue-Song; He, Jia-Yi; Dong, Chen; Ruan, Meng-Ling; Xu, Lei; Bai, Tao; Huang, Zhi-Hua; Shu, Sai-Nan (Frontiers in Pediatrics, 2022)
Background: Fecal microbiota transplantation (FMT) is an effective treatment for intestinal and extraintestinal disorders. Nonetheless, long-term safety and efficacy remain major challenges for FMT applications. To date, few long-term follow-up studies have been published on FMT in children. Methods: Retrospective reviewed the medical charts of 74 patients who underwent 508 FMT courses between August 2014 and July 2019 at our medical center. All the FMT procedures followed uniform standards. Baseline characteristics pre-FMT and follow-up data were collected at 1, 3, 6, 12, 36, 60, and 84 months after FMT. All potential influencing factors for adverse events (AEs) were analyzed and assessed using regression analyses. Results: A total of 70 (13.7%) short-term AEs occurred in twenty-six patients (35.1%). Most AEs (88.5%) occurred within two days post-FMT. A total of 91.4% of the AEs were self-limiting. Ulcerative colitis (UC) and within four times of FMT were associated with a higher rate of AEs (p = 0.028 and p = 0.021, respectively). The primary clinical remission rate after FMT was as high as 72.9%. Twenty-five children were followed for more than 5 years after FMT. The clinical remission rates gradually decreased over time after FMT. During follow-up, none of the patients developed autoimmune, metabolic, or rheumatologic disorders or tumor-related diseases. However, nine children developed rhinitis, five developed rhinitis, were underweight, and six developed constipation. Conclusions: FMT is a safe and effective treatment for dysbiosis in children. The long-term efficacy of FMT for each disease decreased over time. Moreover, multiple FMTs are recommended three months post-FMT for recurrent diseases.